The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12020129
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Patterns, mcr-4 and OXA-48 Genes, and Virulence Factors of Escherichia coli from Apennine Chamois Living in Sympatry with Domestic Species, Italy

Abstract: The aim of this study was to determine and characterize potential resistance mechanisms against selected Critically Important Antibiotics in Escherichia coli isolates collected from wild and domestic ruminants living in the Maiella National Park, in Central Italy. A total of 38 isolates were obtained from red deer, Apennine chamois, cattle, sheep, and goats grazing in lands with different levels of anthropic pressure. Antimicrobial susceptibility was determined by Minimal Inhibitory Concentration testing, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Escherichia coli and enterococci isolated in this study show resistance to a wider range of antibiotics compared to the study carried out in the same protected area on domestic and wild ruminants [ 20 , 21 , 22 ]. Furthermore, the MDR E. coli isolates show resistance to critically important antibiotics (enrofloxacin, marbofloxacin, and pradofloxacin).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Escherichia coli and enterococci isolated in this study show resistance to a wider range of antibiotics compared to the study carried out in the same protected area on domestic and wild ruminants [ 20 , 21 , 22 ]. Furthermore, the MDR E. coli isolates show resistance to critically important antibiotics (enrofloxacin, marbofloxacin, and pradofloxacin).…”
Section: Discussionmentioning
confidence: 54%
“…Antibiotic resistance is a growing concern in both human and animal health, and recent studies have suggested that wildlife may serve as sentinels of antibiotic resistance pollution in the environment [ 18 , 19 , 20 , 21 , 22 ]. Furthermore, the issue of antibiotic resistance in wildlife has important implications for conservation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the resistance genes related to the phenotypic resistance described and identified in this study, the bla TEM gene has been reported in studies involving aquatic bird species performed with culture-independent methods in the USA and Australia [40,41], while bla CMY-1 , mcr-3, and mcr-4 have been described for the first time in the category of animals under investigation. These aforementioned genes have previously been described in other species of domestic and wild animals, as well as in various water sources [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 75%